1999
DOI: 10.1592/phco.19.13.1013.31588
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Molecular‐Weight Heparins in Pregnancy

Abstract: We conducted a systematic review, with MEDLINE and Cochrane Library data base searches and bibliographic reviews, of English-language reports describing therapy with low-molecular-weight heparin (LMWH) in pregnancy. Altogether 40 citations, excluding abstracts, were identified. When the quality of evidence was categorized according to the method outlined by the U.S. Preventive Services Task Force, 2 articles were level I, 3 were level II-1, 3 were level II-2, 4 were level II-3, 9 were level III, and the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 60 publications
0
30
0
3
Order By: Relevance
“…A systematic review of 728 pregnant women treated with LMWH reported 27 (3.7%) bleeding complications. 15 In a smaller review of 57 women prophylaxed or treated with enoxaparin, four (7%) had PPH; vaginal lacerations were the etiologies in two cases. 22 In a large retrospective analysis of 624 pregnancies in 604 women treated with enoxaparin, there were 32 hemorrhages (5.1%) at delivery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A systematic review of 728 pregnant women treated with LMWH reported 27 (3.7%) bleeding complications. 15 In a smaller review of 57 women prophylaxed or treated with enoxaparin, four (7%) had PPH; vaginal lacerations were the etiologies in two cases. 22 In a large retrospective analysis of 624 pregnancies in 604 women treated with enoxaparin, there were 32 hemorrhages (5.1%) at delivery.…”
Section: Discussionmentioning
confidence: 97%
“…11,12 Systematic reviews suggest that enoxaparin therapy appears to be safe and efficacious when used in pregnant women. [13][14][15][16] Because of the longer half-life, the use of LMWH in pregnancy introduces some peripartum management issues. One concern is a risk for significant neuraxial complications from regional anesthesia procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, increased fibrin deposition and consequent placental hypoperfusion are crucial pathogenetic steps [5]. Successful management of pregnancy with thromboprophylaxis regimens in women with a previous history of preeclampsia gives evidence of the fundamental role played by inappropriate coagulation in the pathogenesis of preeclampsia [6].…”
Section: Introductionmentioning
confidence: 99%
“…31 To our knowledge, three reviews systematically evaluated bone complications of long-term LMWH treatment in pregnant participants prone to VTE. [29][30][31] Ensom et al 29 reviewed 40 studies associated with long-term LMWH use in over 700 pregnant women and found two cases of osteoporotic vertebral fractures. Greer et al 30 identified 64 eligible studies in 2777 pregnancies comparing long-term LMWH against control treatments and found one study reporting one vertebral fracture (rate: 0.04 %) in a woman treated with high-dose LMWH (15,000 IU/day) for 9 months.…”
Section: Evidence From Other Studiesmentioning
confidence: 99%
“…The effects of LMWH on bone were mainly studied in the pregnant population. Some research has suggested that long-term LMWH prophylaxis in pregnancy for at least 3 months was associated with bone loss and fractures, [29][30][31] although others have argued that the absolute risk of fracture in this population was small (1-2 %) 32 and that decreases in mean bone mineral density (BMD) of 2-4 % caused by the prophylactic doses of LMWH or unfractionated heparin (UFH) were similar to the bone loss that occurs physiologically during pregnancy. 33,34 Nevertheless, a decrease in BMD of 2-4 % or a small increase in the risk of fracture of up to 2 % would be clinically important for other adult populations such as cancer patients or the elderly who may require long-term LMWH and whose baseline risk of fractures is increased owing to aging or underlying comorbidities.…”
Section: Introductionmentioning
confidence: 99%